(untitled) (REVISTA NODO, 2022)
After the SARS-CoV-2 pandemic, the new normalcy is real and little by little we are assimilating it, so it is necessary to try to clarify the inhabitation of the architectural space together with the pragmatic inquiry of its user. These elements provide an image of the space in which it is possible to appreciate the architectural coexistence as a whole covered under the semiotic theory of signs. There are different ways of understanding architecture, and its design is considered as a formal and functional activity, which due to the cognitive distancing of rationalist architecture, generated a crisis that led to an application of the scientific method with the purpose of freeing itself from all formal concepts, where there is no representation of the space but a configuration linked to the functional value of these (the spaces) and as a consequence the design process advances from the interior to the exterior.